Psychodyanmics of insurgency and economic development - Some reflections in the context of Assam and N.E. States - Baruah, Sriparna B. (2002)
An attempt has been made in this article to determine the meaning and psychological perspectives of insurgency and its relationship with economic development. The entire article has been written in the context of NE region with special reference to Assam which has been taken up as a case study. The economic development of Assam and the rise of insurgency have been studied and the conclusion has been drawn based on the findings of Assam and the NE region. An attempt has also been made to put forward a few recommendations based on the conclusion arrived at. - Reproduced.
Keywords: Economic and social development - India - Assam; Insurgency - India - Assam; Terrorism - India - Assam; Economic and social development - India, North East; Insurgency - India, North East; Terrorism - India, North East; Insurgency - India; Terrorism - India; Terrorism; Assam - Politics and government; Politics and government